Construcción de un reactor piloto para la generación de biodiésel a base de aceite de palma africana(Elaeís guineensis) en la ESPAM MFL - Arias Serrano, Francisco Javier (2016)
This researching aimed BUILD A PILOT REACTOR FOR GENERATING BIODIESEL FROM AFRICAN PALM OIL (Elaeis guineensis) IN ESPAM "MFL", for achieving the objective, the pilot reactor intended to produce biodiesel was assembled according to the technical specifications of the construction Manual and using of Reactor for the production of small-scale biodiesel authoring Acosta, Castro and Cortijo (2008); obtaining biodiesel from palm olein, both clean and reused; plus a User manual to operate the equipment.